Delayed benefit of naps on motor learning in preschool children - Desrochers, Phillip C. (Exp Brain Res, 2015)
Sleep benefits memory consolidation across a variety of domains in young adults. However, while declarative memories benefit from sleep in young children, such improvements are not consistently seen for procedural skill learning. Here we examined whether performance improvements on a procedural task, although not immediately observed, are evident after a longer delay when augmented by overnight sleep (24-hrs after learning). We trained forty-seven children, aged 33–71 months, on a serial reaction time task and, using a within-subject design, evaluated performance at three time points: immediately after learning, after a daytime nap (nap condition) or equivalent wake opportunity (wake condition), and 24-hours after learning. Consistent with previous studies, performance improvements following the nap did not differ from performance improvements following an equivalent interval spent awake. However, significant benefits of the nap were found when performance was assessed 24-hrs after learning. This research demonstrates that motor skill learning is benefited by sleep, but that this benefit is only evident after an extended period of time.